LEAD GEOCHRONOLOGY OF ZIRCON BY LASERPROBE-INDUCTIVELY COUPLED PLASMA MASS SPECTROMETRY (LP-ICPMS) - Feng R.; Ludden J.; Machado N. (My University, 1993)
LaserProbe-inductively coupled plasma mass spectrometry (LP-ICPMS) provides a sensitive, fast, and simple means to determine ages in single zircon grains. A Nd:YAG laser is used to irradiate the zircon surface and leaves a cylindrical pit of 30–60 μm, from which the vaporised materials are transported by argon gas to a Fisons-VG PQII+ ICPMS for analysis. No zircon abrasion, cleaning nor chemical separation procedures are required. The accuracy and the limitation of the method were evaluated by analyzing twenty-one zircon samples ranging in age from 2.7 Ga to 1.0 Ga, which have also been dated by the conventional U-Pb thermal ionization mass spectrometry technique (TIMS). The LP-ICPMS ages for zircons with grain size > 60 μm and 207Pb concentration > 3 ppm are within 1% of the TIMS ages. Smaller zircons (≤60 μm) and those with 207Pb concentration < 2 ppm yield inaccurate ages. Operating the LP-ICPMS at conditions that give a compromise between the ideal spatial resolution and instrument sensitivity, the limits of detection were found to be 0.2 ppm for 206Pb, 207Pb, and 208Pb. The precision of the ratio is generally 0.5–6% (1σ) from each sampling pit and is strongly dependent on the lead concentration. However, the precision for the average of the mean ratios from different pits in one grain or several grains of the same population are generally <1.5% (1σ). The results presented here demonstrate that the LP-ICPMS can be used to determine ages of zircons and that reliable ages can be obtained from high quality, limpid zircons with a simple Pb-loss history. Uses of the technique include screening of zircon populations from different rocks in areas of poorly known age relationships and provenance studies of detrital zircons from ancient and modern sedimentary sequences. Other applications include the study of growth zones and of inherited components in complex zircon populations. In comparison with the SHRIMP (Sensitive High Resolution Ion MicroProbe) technique, the LP-ICPMS has the disadvantage of partially destroying the sample and inability to obtain accurate and precise ratio at present. However, LP-ICPMS has better sensitivity, similar precision, but slightly worse spatial resolution for the measurement of relative to the SHRIMP. Low purchasing and operating cost for the LP-ICPMS provide a simple and economic alternative to the SHRIMP method.